Impact of hyperparathyroidism and its different subtypes on long term graft outcome: a single Transplant Center cohort study - Molinari, Paolo; Regalia, Anna; Leoni, Alessandro; Campise, Mariarosaria; Cresseri, Donata; Cicero, Elisa; Vettoretti, Simone; Nardelli, Luca; Brigati, Emilietta; Favi, Evaldo; Messa, Piergiorgio; Castellano, Giuseppe; et al. (Frontiers in Medicine, 2023)
Purpose We studied the association between parathormone (PTH) levels and long-term graft loss in RTx patients (RTx-p). Methods We retrospectively evaluated 871 RTx-p, transplanted in our unit from Jan-2004 to Dec-2020 assessing renal function and mineral metabolism parameters at 1, 6, and 12 months after RTx. Graft loss and death with functioning graft during follow-up (FU, 8.3[5.4–11.4] years) were checked. Results At month-1, 79% had HPT, of which 63% with secondary HPT (SHPT) and 16% tertiary HPT (THPT); at month-6, HPT prevalence was 80% of which SHPT 64% and THPT 16%; at month-12 HPT prevalence was 77% of which SHPT 62% and THPT 15%. A strong significant correlation was found between HPT type, PTH levels and graft loss at every time point. Mean PTH exposure remained strongly and independently associated to long term graft loss (OR 3.1 [1.4–7.1], p = 0.008). THPT was independently associated with graft loss at month-1 when compared to HPT absence and at every time point when compared to SHPT. No correlation was found with RTx-p death. Discriminatory analyses identified the best mean PTH cut-off to predict long-term graft loss to be between 88.6 and 89.9 pg/mL (AUC = 0.658). Cox regression analyses highlighted that THPT was strongly associated with shorter long-term graft survival at every time-point considered. Conclusion High PTH levels during 1st year of RTx seem to be associated with long term graft loss.